How microplastics quantities increase with flood events? An example from Mersin Bay NE Levantine coast of Turkey - Gundogdu, Sedat; Cevik, Cem; Ayat, Berna; Aydogan, Burak; Karaca, Serkan (ELSEVIER SCI LTD, 2018)
Floods caused by heavy rain carry significant amounts of pollutants into marine environments. This study evaluates the effect of multiple floods that occurred in the northeastern Mediterranean region in Turkey between December 2016 and January 2017 on the microplastic pollution in the Mersin Bay. Sampling was repeated in four different stations both before and after the flood period, and it was determined that in the four stations, there was an average of 539,189 MPs/km(2) before the flood, and 7,699,716 MPs/km(2) afterwards, representing a 14-fold increase. Fourteen different polymer types were detected in an ATR FT-IR analysis, eight of which were not found in samples collected before the floods. The most common polymer type was identified as polyethylene both pre- and post-flood. The mean particle size, which was 2.37 mm in the pre-flood period, decreased to 1.13 mm in the post-flood period. A hydrodynamic modeling study was implemented to hindcast the current structure and the spatial and temporal distributions of microplastics within the study area. In conclusion, heavy rain and severe floods can dramatically increase the microplastic levels in the sea. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: Microplastic; Marine litter; Levantine sea; Mersin bay; Rain flood; ATR FT-IR; MARINE-ENVIRONMENT; PLASTIC DEBRIS; PACIFIC-OCEAN; POLLUTION; SEA; ACCUMULATION; DYNAMICS; PELLETS; IMPACT; WATERS; Environmental Sciences & Ecology